Various Community Motivations for the Success of Ecosystem Restoration in Mount Baung Nature Park, Pasuruan Regency - Asep Hawim Sudrajat; Surjono Surjono; Jati Batoro (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
Mount Baung is a conservation forest area located in Pasuruan Regency. In this area, there is an area of 27 ha that has been damaged. Research on the motivation of local communities in supporting the success of ecosystem recovery is very important to obtain an overview of the situation of high exclusion costs in the use of forest resources in Mount Baung Nature Park. Research methods are quantitatively presented in statistical data through the analysis of validity, ratability, multiple linear regression and determination. The regression test analysis value was Sig 0.559. It can be concluded if the regression value is significant. Then it was found that there were 11 variables that were very influential. The high determining factors to be able to increase community motivation in the management of Mount Baung are monitoring and assessing the results of ecosystem management, utilizing the results of Mount Baung Nature Park management of Mount Baung, the role of program managers (BKSDA), the desire to increase income. Support community/government leaders and community initiatives. As an effort to manage the sustainable Mount Baung Nature Park of Mount Baung, the determining factors to increase community motivation need to be an important consideration in community assistance.